Pharmacological and electronic cigarette interventions for smoking cessation in adults: component network meta-analyses - Lindson, N; Theodoulou, A; Ordóñez-Mena, JM; Fanshawe, TR; Sutton, AJ; Livingstone-Banks, J; Hajizadeh, A; Zhu, S; Aveyard, P; Freeman, SC; Agrawal, S; Hartmann-Boyce, J (Cochrane Collaboration, 2023)
Background Tobacco smoking is the leading preventable cause of death and disease worldwide. Stopping smoking can reduce this harm and many people would like to stop. There are a number of medicines licenced to help people quit globally, and e‐cigarettes are used for this purpose in many countries. Typically treatments work by reducing cravings to smoke, thus aiding initial abstinence and preventing relapse. More information on comparative effects of these treatments is needed to inform treatment decisions and policies. Objectives To investigate the comparative benefits, harms and tolerability of different smoking cessation pharmacotherapies and e‐cigarettes, when used to help people stop smoking tobacco. Search methods We identified studies from recent updates of Cochrane Reviews investigating our interventions of interest. We updated the searches for each review using the Cochrane Tobacco Addiction Group (TAG) specialised register to 29 April 2022. Selection criteria We included randomised controlled trials (RCTs), cluster‐RCTs and factorial RCTs, which measured smoking cessation at six months or longer, recruited adults who smoked combustible cigarettes at enrolment (excluding pregnant people) and randomised them to approved pharmacotherapies and technologies used for smoking cessation worldwide (varenicline, cytisine, nortriptyline, bupropion, nicotine replacement therapy (NRT) and e‐cigarettes) versus no pharmacological intervention, placebo (control) or another approved pharmacotherapy. Studies providing co‐interventions (e.g. behavioural support) were eligible if the co‐intervention was provided equally to study arms. Data collection and analysis We followed standard Cochrane methods for screening, data extraction and risk of bias (RoB) assessment (using the RoB 1 tool). Primary outcome measures were smoking cessation at six months or longer, and the number of people reporting serious adverse events (SAEs). We also measured withdrawals due to treatment. We used Bayesian component network meta‐analyses (cNMA) to examine intervention type, delivery mode, dose, duration, timing in relation to quit day and tapering of nicotine dose, using odds ratios (OR) and 95% credibility intervals (CrIs). We calculated an effect estimate for combination NRT using an additive model. We evaluated the influence of population and study characteristics, provision of behavioural support and control arm rates using meta‐regression. We evaluated certainty using GRADE. Main results Of our 332 eligible RCTs, 319 (835 study arms, 157,179 participants) provided sufficient data to be included in our cNMA. Of these, we judged 51 to be at low risk of bias overall, 104 at high risk and 164 at unclear risk, and 118 reported pharmaceutical or e‐cigarette/tobacco industry funding. Removing studies at high risk of bias did not change our interpretation of the results. Benefits